Pengamatan Lingkungan Pengelolaan Pasar Tradisional di Kabupaten Sumedang - Sudrajat, Arip Rahman; Sumaryana, Asep; Buchari, Raden Ahmad; Tahjan, Tahjan (Jurnal Administrasi Publik : Public Administration Journal, 2019)
This research is about observing the environment in managing Traditional Markets in Sumedang Regency. Problems involving external analysis are characterized by a lack of representation of facilities and infrastructure and limited storage of work documents, while internal analysis is characterized by assigning tasks to employees that are not based on the competencies of each employee. The theory used refers to the stages in strategic management that refer to one element of the four basic elements of strategic management, namely environmental observation. The method in this study uses a qualitative approach. The results showed that in the external analysis aspect carried out by the Department of Cooperatives, Small and Medium Enterprises, Trade and Industry of Sumedang Regency, not yet fully able to analyze the external conditions, namely the work environment and social environment in the Cooperative, Small and Medium Enterprises, Trade and Industry Sumedang Regency is to be used as a strength or carrying capacity in the implementation of strategic management of Traditional Market management in Sumedang Regency, marked by facilities and infrastructure to support a limited working environment and social environment that still leaves social problems from the weak handling of garbage and placement of street vendors. While internal analysis on cultural aspects must be improved in terms of employee work discipline and human resource competencies must be improved according to work completion requirements.